Assessment of hypothetical correlation between the various critical factors for lean systems in automobile industries. (2020) - Arunagiri, P.; Suresh, P.; Jayakumar, V.
Abstract: Lean production system leads to the elimination of non value added activities in the industrial environment and restructure the existing production procedures and processes to achieve improvements in terms of cost reduction, increase in quality and profit. The purpose of this paper is to identify the critical factors of lean Implementation and to evaluate their role of critical factors in organizational performance. The following factors are considered to measure the impact of lean system such as business type, period of usage of lean, type of benefits achieved from lean, lean activity occurrence, turnover rate, Employee training, customer satisfaction percentage, lean activity interval, the delivery defect rate in Indian automobile industries. To achieve these objectives a empirical study was conducted through 83 copies of questionnaire which is circulated to various employees attended the manufacturing exhibition in India. Frequency analysis is carried out for eight critical factors for lean implementation. The cross tabulation is charted out in order to find the hypothetical relations between the various factors. Each factor influences the lean production success, which is proved using the hypothesis testing. Hypothetical findings based on the survey reveal that successful lean implementation can positively affect both employees and industrial performance in Indian automobile industries.